1999
DOI: 10.1002/(sici)1521-396x(199907)174:1<5::aid-pssa5>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Structural Aspects of CVD Diamond Wafers Grown at Different Hydrogen Flow Rates

Abstract: Microstructural modifications of thick diamond films grown by microwave plasma CVD at different reactant gas flow rates have been studied by transmission electron microscopy. A strong degradation of the diamond quality was observed at low hydrogen flow rates, while the layer grown at the highest hydrogen flow rate was almost defect free. The abundance of various defects observed, mostly microtwins, stacking faults, dislocations and even amorphous regions, clearly correlates with the gas flow rate. Illustration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…This might be due to the fast gas exchange that occurs in the presence of high methane and hydrogen concentration in the reaction chamber. 35 The varied density of defects from sample W1 to W3 suggests that different experimental growth conditions promote different crystallographic defects. In case of W3, the diamond grains grew with crystallographic orientations that favour nucleation of stacking faults and twins to relax the stress, while in W1 the growth of diamond grains took place under stress generating defects like dislocations.…”
Section: Characterization Of Coating Deposited After Process Optimizamentioning
confidence: 99%
“…This might be due to the fast gas exchange that occurs in the presence of high methane and hydrogen concentration in the reaction chamber. 35 The varied density of defects from sample W1 to W3 suggests that different experimental growth conditions promote different crystallographic defects. In case of W3, the diamond grains grew with crystallographic orientations that favour nucleation of stacking faults and twins to relax the stress, while in W1 the growth of diamond grains took place under stress generating defects like dislocations.…”
Section: Characterization Of Coating Deposited After Process Optimizamentioning
confidence: 99%
“…The densities of such defects have been found to be controlled by CVD growth parameters, viz., flow rate of hydrogen, percentage of methane and substrate temperature. 10,11 The density of crystal defects and the amount of non-diamond phases present in the diamond coating determine its shade, ranging from black to grey towards white and hence its suitability to different applications. Diamond coatings appearing dark under optical microscope contain high density of defects and can be used only for tribological applications and cannot be used as an optical component in instruments, e.g., gyrotron windows, X-ray optics, infrared spectrometer, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It is now known that 'whiteness' and 'darkness' of diamond can be manipulated by suitably varying the deposition parameters. 10,13 Polycrystalline diamond (PCD) coatings grown by the microwave plasma enhanced chemical vapour deposition (MWPECVD) technique is used as window material for millimetre wave transmission in gyrotron tubes. Such material can be grown by the CVD technique into different grades like thermal grade, mechanical grade, optical grade, electronic grade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 This increase in boron embedding at higher methane ratios during film growth is the result of an increased presence of defects and non-sp 3 carbon in NCD films grown under high methane concentrations. 15,16 As the defects in B:NCD are known to be enriched in B, 7 the average B concentration in films grown under high methane ratios is therefore elevated. 17 Theoretical work has shown that the r* feature in the EELS C K-edge is highly sensitive to the local C bond length.…”
mentioning
confidence: 99%